2021
DOI: 10.1007/s00586-021-07035-4
|View full text |Cite
|
Sign up to set email alerts
|

Motion preservation surgery for scoliosis with a vertebral body tethering system: a biomechanical study

Abstract: Purpose There is a paucity of studies on new vertebral body tethering (VBT) surgical constructs especially regarding their potentially motion-preserving ability. This study analyses their effects on the ROM of the spine. Methods Human spines (T10-L3) were tested under pure moment in four different conditions: (1) native, (2) instrumented with one tether continuously connected in all vertebrae from T10 to L3, (3) additional instrumented with a second tether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Unfortunately, there are no biomechanical studies providing evidence for greater strength of double cords, although such an assumption was made by Baroncini et al 37 A recent biomechanical study demonstrated that single or double cords did not significantly differ in restricting global and L1-L2 spinal range of motion in flexion or extension (<10%) and left or right axial rotation (<14%). 30 In addition, it was shown, that intervertebral discs and facet joints do not undergo degenerative changes after an average of 29 months of follow-up in dynamic correction surgery. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there are no biomechanical studies providing evidence for greater strength of double cords, although such an assumption was made by Baroncini et al 37 A recent biomechanical study demonstrated that single or double cords did not significantly differ in restricting global and L1-L2 spinal range of motion in flexion or extension (<10%) and left or right axial rotation (<14%). 30 In addition, it was shown, that intervertebral discs and facet joints do not undergo degenerative changes after an average of 29 months of follow-up in dynamic correction surgery. 38 …”
Section: Discussionmentioning
confidence: 99%
“… 5 , 29 Dynamic correction allows for preserved mobility in the instrumented region, which has been confirmed by biomechanical studies. 30 Furthermore, dynamic correction allows patients to return to their usual physical activity and sports within a relatively early timeframe. 31 …”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of vertebral body tethering is to keep spine mobility. A lot of studies demonstrate that this mobility helps to compensate sagittal issues and that a loss of lumbar mobility could lead to functional disability [11,12,16,17,[22][23][24][25][26]. The posterior Wiltse approach respects spine mobility as much as an anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency was adjusted to 3 Hz. The total number of cycles was set to 250,000 (and 500,000 for titanium) which roughly represents the amount of chewing cycles per year [ 16 ] and was recorded at a frequency of 100 Hz [ 18 ]. Testing was stopped in case of plate or screw failure or significant deformation of osteosynthesis materials; cycles were then recorded up to the point of failure.…”
Section: Methodsmentioning
confidence: 99%